2019
DOI: 10.3390/atmos10070408
|View full text |Cite
|
Sign up to set email alerts
|

No Particle Mass Enhancement from Induced Atmospheric Ageing at a Rural Site in Northern Europe

Abstract: A large portion of atmospheric aerosol particles consists of secondary material produced by oxidation reactions. The relative importance of secondary organic aerosol (SOA) can increase with improved emission regulations. A relatively simple way to study potential particle formation in the atmosphere is by using oxidation flow reactors (OFRs) which simulate atmospheric ageing. Here we report on the first ambient OFR ageing experiment in Europe, coupled with scanning mobility particle sizer (SMPS), aerosol mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Further, the fact that the reactor was kept in an air-conditioned space increases the losses when it is colder outside (e.g. during nights), which was also seen by Ahlberg et al (2019). No trend in the enhancement of particle mass with OH exposure was seen, likely due to the comparably low exposures.…”
Section: Simulation Of Atmospheric Processingmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, the fact that the reactor was kept in an air-conditioned space increases the losses when it is colder outside (e.g. during nights), which was also seen by Ahlberg et al (2019). No trend in the enhancement of particle mass with OH exposure was seen, likely due to the comparably low exposures.…”
Section: Simulation Of Atmospheric Processingmentioning
confidence: 96%
“…There are several other parameters which affect the absolute emission of PM as well as the particle composition, such as fuel type, operation conditions, engine load, engine properties, and maintenance. Ship exhaust also contains elevated levels of nitrogen oxides (NO x , including NO 2 and NO), sulfur dioxide (SO 2 ), carbon monoxide (CO), carbon dioxide (CO 2 ), and volatile organic compounds (VOCs) (Sinha et al, 2003;Chen et al, 2005;Alföldy et al, 2013;Moldanová et al, 2009;Huang et al, 2018;Cooper, 2001). Concentrations of CO 2 can be used to estimate emission factors of gases and particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OFRs can be used for qualitatively observing ships that contribute a lot to secondary aerosol inland, but should preferably be placed closer to the shipping lanes. Care must also be taken to ensure that reported secondary particle formation is not influenced by the background condensation sink (Palm et al, 2016;Ahlberg et al, 2019). 360…”
Section: Simulation Of Atmospheric Processingmentioning
confidence: 99%
“…Aerosol particles are both primarily emitted in the atmosphere and secondarily formed from atmospheric processing of organic and inorganic precursors, with the secondary organic aerosol (SOA) constituting a substantial fraction of the mass of submicron aerosol in populated areas around the world; this contributes to poor air quality and premature mortality [9]. In the first ambient oxidation flow reactor measurements in Europe, Ahlberg et al [4] demonstrated that there was no increase in particle mass or number concentrations during the two months of the campaign, which was primarily attributed to limited gaseous precursor concentrations and, to a lesser extent, to a net particle mass loss of ~10%, correlated to ambient temperature and OH exposure. It was shown that, with ambient PM 1 concentrations in the order of 3 µg m −3 , one order of magnitude higher precursor concentrations would have been needed to form significant amounts of SOA in the reactor.…”
mentioning
confidence: 99%